Casting Homogeneity of Scaled-Up Multiprincipal Component Alloys - Gbenga. J. Adeyemi; Claire Utton; Yunus Azakli; Russell Goodall (Journal of Manufacturing and Materials Processing)
High-entropy and multicomponent alloys are believed to offer opportunities for improved properties and are currently of great interest to the research community. Studies on these materials are largely conducted on small samples, but, for many practical applications, larger-scale processing would be needed. The processing of metallic parts of high dimensionality conventionally begins with casting, but an increase in the scale of the melt increases the potential for effects dependent on segregation, diffusion and thermal transport. The objective here is to determine the effect of scale-up on the as-cast condition of an example multicomponent alloy, Cu-Zn-Mn-Ni medium-entropy (ME) brass, in a larger quantity. The ingot was produced by metallic mould casting after induction melting. The hardness, microstructures and chemical composition were assessed in the as-cast state across a section through the material. A range of hardness values were found, particularly in the vertical direction, where the upper region was found to have a hardness of 188 ± 15 HV0.5, a middle of 161 ± 11 HV0.5 and a bottom of 184 ± 16 HV0.5. These values can be correlated with the casting conditions experienced locally, but the average hardness values are close to that of the original reports of the alloy. To overcome this, it is likely that a heat treatment would need to be used for this alloy in practical production before the products could be applied for engineering uses.